Ways to promote the efficiency of herpetic stomatitis treatment - R.V. Lutsenko; N.V. Moisieieva; A.H. Sydorenko; H.Yu. Ostrovska; A.A. Kapustianska (Medičnì Perspektivi)
The treatment of herpetic stomatitis should be etiotropic, pathogenetic, symptomatic, and local. The research determined the effectiveness of inosine pranobex (1000 mg 4 times a day) in herpetic stomatitis treatment. Addition of inosine pranobex to the pharmacotherapy of herpetic stomatitis reduced hospital stay and duration of treatment. The drug suppresses the synthesis of the virus due to the structure of inosinic acid in the polyribosomes of the cell affected by the virus, and also helps to eliminate the deficiency or dysfunction of immunity that occurred in the case of herpetic stomatitis, it affects the activity of T-cytotoxic lymphocytes and natural killers, enhances the action of neutrophil granulocytes, chemotaxis and phagocytosis of monocytes and macrophages, increases the synthesis of interleukins IL-1 and IL-2, affects the number of Ig G immunoglobulins. Applying inosine pranobex also significantly decreased pain syndrome manifestations from the start of the treatment. It contributed to body temperature normalization 2 days earlier which shortened the treatment period at the in-patient department. Applying inosine pranobex in the combination therapy of herpetic stomatitis has shown a potent clinical efficacy and can be an alternatіve to acyclic nucleosides in patients with herpetic stomatitis of the oral mucosa.